Analysis of The Causes of Defects In Products in Cup Filing Machines : Analisa Penyebab Cacat Pada Produk di Mesin Filing Cup - Efendi, Moch Miqdar; Tjahjanti, Prantasi Harmi (Procedia of Engineering and Life Science, 2024)
Drinking water is good water and can be in natural form or processed like sea water for desalination, itmust meet the drinking water standards set. Drinking water standards are divided into ordinary water, mineral water, natural mineral water and bottled water. AMDK is drinking water that has been treated, packaged and is safe for direct consumption in accordance with industrial standards in Indonesia. Manufacturing machines including glass, bottle and gallon filling machines often experience product defects outside the planned schedule and machine damage causes production to stop, thereby reducing machine performance and suggestions and input for improvements so that it can run as desired.